Assimilating atmospheric carbon dioxide in tea gardens of northeast India. (15th February 2020) - Pramanik, Prabhat; Phukan, Manabjyoti
Abstract: Carbon dioxide (CO2 ) is the most important greenhouse gas in the atmosphere and phyto-assimilation is the most effective technique to mitigate global warming effect of CO2 gas in the atmosphere. Tea is an evergreen perennial plant and cultivated worldwide under subtropical humid climatic condition for harvesting its tender shoots. Tea bushes of different cultivars and ages are grown in combination to minimize possible adverse effect of biotic and abiotic stresses; hence distribution of tea plantation in a tea garden is complex in nature. Large shade trees are also an integral part of tea garden. Those plantations in tea garden have huge potential to capture atmospheric CO2 ; however, ability of tea bushes to mitigate global warming while producing tea shoots is not quantified before. The objective of this study was to quantify the potential of tea plantation to mitigate greenhouse effect (global warming mitigation potential, GWMP) due to assimilation of atmospheric CO2 gas. High yielding TV23 cultivar assimilated significantly higher amount of CO2 as compared to quality tea producing cultivars (S3A/3) and mature 25–30 years old tea bushes absorb more CO2 from the atmosphere as compared to younger tea bushes. Considering the mixed population of cultivars in tea gardens, overall, tea bushes sequestrated 5134.4 ± 831.6 kg CO2 ha −1 yr −1 in their biomass and had GWMP 3.47 ± 0.64 kg CO2 KMTH −1 yr −1 . Shade trees sequestrated 4037.4 ± 589.9 kg CO2 ha yr −1 from the atmosphere. Hence, the GWMP of whole plantation ((both tea bushes and shade trees) was 6.19 ± 1.7 kg CO2 KMTH −1 yr −1 . In this study, tea bushes sequestrated 52.7–61.3% of the total CO2 sequestrated by the plantations in tea garden. This study enabled to understand that tea bushes play significant role in mitigating global warming by assimilating and sequestrating atmospheric CO2 and the estimated value of global warming mitigation potential may be used for direct estimation of C sequestration by plantations in tea garden using its productivity value. Highlights: Tea bushes sequestrated 5134.4 ± 831.6 kg CO2 ha −1 yr −1 in their biomass. Global warming mitigation potential of tea bushes was 3.47 ± 0.64 kg CO2 KMTH −1 yr −1 . Total C-sequestration potential of shade trees was 4037.4 ± 589.9 kg CO2 ha yr −1 . GWMP of tea bushes along with shade trees was 6.19 ± 1.7 kg CO2 KMTH −1 yr −1 .